Prevalence and related factors of physical function and cognitive impairment among older adults: a population-based regional cross-sectional study - Zhang, Yi; Cheng, Guifen; Chen, Ling; Wang, Xiaoxia; Lin, Lixia; Huang, Qiao; Guo, Jinhua; Gong, Bei; Shen, Tiemei (Frontiers in Aging Neuroscience, 2025)
Background and aimsAs the country with the largest and fastest-aging older population worldwide, China has hosted an increasing number of regional investigations into disability among older adults. However, the prevalence of disabilities related to physical function and cognition in southern China remains unknown. This study aimed to assess the prevalence of and associated factors for cognitive and physical function impairment in individuals aged 60 years and older.MethodsFor this population-based cross-sectional study, a total of 5,603 participants were recruited between June 2021 and December 2022 using a multistage, stratified, cluster sampling procedure. Instruments, including a general questionnaire, basic and instrumental activities of daily living, the Chinese version of the Mini-Mental State Examination (MMSE), the Patient Health Questionnaire-9 (PHQ-9), and the Generalized Anxiety Disorder-7 (GAD-7), were used to collect data through a WeChat mini program. Binary and multivariate logistic regression analyses were applied to explore the influencing factors.ResultsThe prevalence of physical function and cognitive impairment among older adults was 37.3 and 31.0%, respectively. Multivariate regression analyses revealed that age, family income, education level, place of residence, medication type, annual physical examinations, weekly social activities, support from family or friends, hearing disorders, walking disorders, and depression were all associated with both physical function and cognitive impairment. Moreover, an increased risk of physical function impairment correlated with BMI, region, income source, smoking, and weekly exercise, while cognitive impairment was associated with the number of children, insurance type, coronary heart disease, and anxiety. Physical function (OR: 1.79, 95% CI: 1.49–2.16) and cognitive impairment (OR: 1.83, 95% CI: 1.51–2.21) were mutually influential in our study.ConclusionThis study showed a high prevalence of various factors related to physical function and cognitive impairment. The results revealed that comprehensive and systematic prevention and control programs for disabilities should be developed to improve the quality of life for older adults.